2016
DOI: 10.1159/000454830
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of Intravenous Administration of CD34<sup>+</sup> Human Umbilical Cord Blood Cells in a Mouse Model of Neonatal Hypoxic-Ischemic Encephalopathy

Abstract: Several cell therapies have been explored as novel therapeutic strategies for neonatal encephalopathy because the benefits of current treatments are limited. We previously reported that intravenous administration of human umbilical cord blood (hUCB) CD34+ cells (hematopoietic stem cells/endothelial progenitor cells) at 48 h after insult exerts therapeutic effects in neonatal mice with stroke, i.e., permanent middle cerebral artery occlusion. Although neonatal stroke and hypoxic-ischemic encephalopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…In the literature, almost all preclinical studies on neonatal brain injuries examined the effects of UCBC administration at only one timepoint. Many such studies reported beneficial effects of UCBC administration at 24 or 48 hours after brain injury 11,12,15,17,18,22,24,25,35 . Preclinical studies on other types of cells and/or in other models have demonstrated that early administration, i.e., a few hours after brain injury is not as beneficial as later administration, such as 24-72 hours after brain injury 36 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, almost all preclinical studies on neonatal brain injuries examined the effects of UCBC administration at only one timepoint. Many such studies reported beneficial effects of UCBC administration at 24 or 48 hours after brain injury 11,12,15,17,18,22,24,25,35 . Preclinical studies on other types of cells and/or in other models have demonstrated that early administration, i.e., a few hours after brain injury is not as beneficial as later administration, such as 24-72 hours after brain injury 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Our research group, named the Neonatal Encephalopathy Consortium Japan, conducted preclinical studies before translating UCBC therapy to the clinic. We demonstrated that the intravenous infusion of human CD34 + cells (haematopoietic stem/endothelial progenitor cells) at 48 hours after brain injury partially ameliorated the damage in mouse models of neonatal stroke 18 and neonatal HIE 22 . Additionally, we have demonstrated that intraperitoneal infusion of the MNC fraction of human UCBCs at 6 hours after brain injury partially ameliorates the damage in a rat model of neonatal HIE 19 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…even one week after hypoxia-ischemia. However, some groups have reported that intravenous administration of human UCBCs 24 or 48 hours after hypoxia-ischemia in rodent models leads to no significant improvement in either brain injuries or motor function (de Paula et al , 2009; Ohshima et al , 2016). Thus, a number of parameters, such as optimal dose, timing, administration route, duration of therapy, and immunosuppression, still need to be further investigated in order to provide better guidance for the full translation to clinical applications.…”
Section: Bench To Bedside: Promising Anti-inflammatory/immunomodulmentioning
confidence: 99%
“…Forelimb functional impairment was evaluated in cylinder tests 7 days after the surgery (P19), as previously described ( 20 ). We placed each mouse in a transparent cylinder (14 cm inner diameter and 30 cm high) and video recorded its behavior until it reared and touched the cylinder wall with its forepaw(s) a minimum of 20 times.…”
Section: Methodsmentioning
confidence: 99%